Perancangan Katalog Digital Museum Radya Pustaka Surakarta - Handita Kesoema, Ivan; Handriyotopo, Handriyotopo (ISI Press Institut Seni Indonesia Surakarta, 2022)
Radya Pustaka Surakarta Museum needs a service that is able to efficiently present information about its 15,216 collection of cultural heritage objects. The design of the digital catalog website interface aims to be an information service medium for the Radya Pustaka Surakarta Museum that can help visitors find information on cultural heritage. Design using the Design Thinking method is human centered or focuses on human needs (users) and the process originates and is aimed at users. The results of the design include product identity (verbal and visual) from a digital catalog with the main identity of Rajamala combined with primary colors of blue, yellow, and white with a flat design illustration style referring to Michael Fugoso's style and shadows in wayang performances. The main media for this design are website prototypes and promotional media (Instagram campaigns, digital posters and YouTube advertisements) and merchandise supporting media such as (t-shirts, tumblers, sitting calendars, wall clocks, notebooks, keychains, enamel pins and sticker sets).